The Diasporic Rejection and Doubleness in Ayesha at Last - Muhammad Fayyad (STKIP PGRI Lubuklinggau, 2023)
AbstractThe diasporic issues, including rejection and doubleness of cultural identities, are still existent and requiring attention and solutions. These issues may be expressed in the form of diasporic literature. The article used the concepts of rejection and doubleness of cultural identity to analyze the novel. The researchers analyze the novel Ayesha at Last which contains diasporic characters and issues in order to highlight the problems diasporic people encounter expressed in the novel. The main issues that are analyzed are the diasporic rejection and doubleness of cultural identity. The article found these problems and issues of rejection and doubleness faced by the diasporic characters in the novel. The article concluded that these rejections and doubleness in diaspora found in the novel is an expression of the real world issues the diaspora community faces. Keywords: Doubleness, Rejection, Diaspora